Recruitment Advertising: Art and Adventure in Indian Press Ads - George, Ruby; Manickam, Evangeline; Jayachandran, S. (Indian Journal of Marketing, 2008)
The quality and contribution of the people are the key differentiators in all organizations. Recruiting manpower is, therefore, of paramount importance to fill up vacancies and to build up an efficient, motivated workforce. Advertising is a valuable tool which enables the recruiter to induct eligible personnel in the most cost-effective manner. This paper dwells on the newspaper resume ads and makes an in-depth analysis of two specialized types of press ads: Classified Lineage and Display ads. It elaborates on the content as well as the creative strategies that characterize recruitment advertising. While discussing the classifieds it takes into account the on-going quest for brevity and visibility. The display ads, which enjoy greater graphic freedom, are a revelation of the ways and means by which the recruiters are creating a niche for themselves in the hearts and minds of the readers. It also discusses the manifold ways in which the print media supports and promotes recruitment advertising. This paper emphasizes the importance of appraising/updating manpower requirements and constructing a meaningful rapport with the target audience.